2018
DOI: 10.1016/j.ajo.2018.07.045
|View full text |Cite
|
Sign up to set email alerts
|

Gene Expression Profiling and PRAME Status Versus Tumor-Node-Metastasis Staging for Prognostication in Uveal Melanoma

Abstract: In UM, molecular prognostic testing using GEP and PRAME provides prognostic accuracy that is superior to TNM staging.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
37
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(39 citation statements)
references
References 27 publications
2
37
0
Order By: Relevance
“…29 Moreover, it has been demonstrated by other groups that incorporating clinical, histologic, and genomic information from GEP and other validated commercial tests can enhance prognostication in a more individualized manner. [13][14][15][16][17]30 As GEP and AJCC are among the most commonly employed prognostic tools, further exploration of their particular relationship is a necessary step towards providing the most accurate prognostic information to our patients.…”
Section: Discussionmentioning
confidence: 99%
“…29 Moreover, it has been demonstrated by other groups that incorporating clinical, histologic, and genomic information from GEP and other validated commercial tests can enhance prognostication in a more individualized manner. [13][14][15][16][17]30 As GEP and AJCC are among the most commonly employed prognostic tools, further exploration of their particular relationship is a necessary step towards providing the most accurate prognostic information to our patients.…”
Section: Discussionmentioning
confidence: 99%
“…To determine patients at higher risk for developing metastatic disease, clinical or histopathologic risk factors are considered [ 2 ]. More recently, gene expression analysis (i.e., gene expression profiling [GEP] and preferentially expressed antigen in melanoma [PRAME] status) after direct surgical tumor sampling has enhanced prognostic accuracy [ 3 5 ]. While tumor biopsies are beneficial for assessing mortality risk, they are still subject to certain risks (e.g., risk of retinal detachment and tumor dissemination) and not amenable to repeat testing [ 3 5 ].…”
Section: Main Textmentioning
confidence: 99%
“…We found that the prognostic model based on LBTD alone performed reasonably well across the time range of 2 to10 years (C-indices, 0.74–0.79) without the inclusion of ciliary body involvement, tumor thickness, and extraocular spread. Cai et al 32 reported similar findings. These predictors would have improved prognostication slightly, as with TNM staging (C-indices, 0.76–0.81).…”
Section: Discussionmentioning
confidence: 56%
“…This committee may also investigate whether to retain or omit predictors that lose significance (i.e., ciliary body involvement and tumor thickness) when genetic data are entered into their models, as we have shown in this study and as others have shown previously. 32 If our approach is validated externally and adopted by the AJCC committee, it may increase the uptake of TNM staging if generally found to be more convenient than the current system, especially as it allows anatomic predictors to be combined with genetic data. Some authors favor gene expression profiling, but this is not widely available outside the United States.…”
Section: Discussionmentioning
confidence: 99%